Selected Lectures of the 13th International Workshop on Neonatology; Cagliari (Italy); October 25th-28th, 2017 - - (Hygeia Press di Corridori Marinella, 2017)
Selected Lectures of the 13th International Workshop on Neonatology • The power of Epigenetics • Twins: identical but different • Cagliari (Italy) • October 25th-28th, 2017 LECT 1. ASPHYXIA IN THE THIRD MILLENNIUM: FROM VIRGINIA APGAR TO METABOLOMICS • O.D. Saugstad LECT 2. INTRAPARTUM FETAL MONITORING: WHERE ARE WE NOW? • D. Ayres-de-Campos LECT 3. THERAPEUTIC HYPOTHERMIA: REVISED INDICATIONS • E. Saliba LECT 4. ANTIBIOTICS PRESCRIPTION IN NEONATAL INTENSIVE CARE UNIT • G. Dimitriou LECT 5. CHORIOAMNIONITIS: FROM CLASSIC DATA TO METABOLOMICS • L. Pugni, C. Fattuoni, C. Pietrasanta, A. Ronchi, A. Noto, L. Barberini, F. Mosca, V. Fanos LECT 6. FUNGAL INFECTIONS • A. Giannattasio, L. Capasso, T. Ferrara, S. Salomè, A. Umbaldo, R. Albachiara, F. Raimondi LECT 7. METABOLOMICS IN SEPSIS: THE POWER OF PREDICTION • V. Fanos, R. Pintus, A. Noto, A. Dessì LECT 8. PROBIOTICS IN OBSTETRICS and GYNAECOLOGY • G. Ettore, E. Palma, N. Recine, L. Ferrara, C. Ettore LECT 9. LATE PRETERM INFANTS WITH RESPIRATORY DISTRESS SYNDROME: LIGHTS AND SHADOWS • C. Dani LECT 10. PRECISION VENTILATION IN NEWBORN • P.E. Tagliabue, M.L. Ventura, E. Zannin, R. Dellacà LECT 11. PRECISION NON-INVASIVE VENTILATION IN NEWBORNS • C. Moretti, F. Midulla, C.S. Barbara, R. Nenna, L. Di Lucchio, C. Gizzi LECT 12. BRONCHOPULMONARY DYSPLASIA: FROM NORTHWAY TO METABOLOMICS • D. Manus, V. Masile, M.C. Pintus, A. Dessì, V. Fanos LECT 13. RESPIRATORY SYNCYTIAL VIRUS INFECTION: WHAT'S NEW? • M. Lanari, C. Biagi LECT 14. EMERGENCY IN OBSTETRICS, WORLDWIDE • R. Baiocchi, K. Picucci, E. Bruni LECT 15. NEONATOLOGY IN AFGHANISTAN • M. Testa LECT 16. NEW PERSPECTIVES IN HUMAN MILK FORTIFIERS • E. Bertino, G.E. Moro, P. Tonetto, C. Peila, L. Occhi, E. Spada, G. Ansaldi, S. Deantoni, L. Cavallarin, M. Giribaldi, A. Coscia, A. Dessì, V. Fanos LECT 17. GUT PERTURBATION AND PROBIOTICS IN NEONATOLOGY • G. Biasucci LECT 18. NEAR INFRARED SPECTROSCOPY AND GUT FUNCTION IN PRETERM NEWBORNS • L. Corvaglia, S. Martini LECT 19. ALLERGY TO COW'S MILK PROTEIN • M. De Filippo, A. Licari, G.L. Marseglia LECT 20. GLOMERULAR NUMBER IN LBW BABIES: NOTE FOR THE FUTURE. THE FAULT IS NOT IN OUR STARS BUT MAY BE IN OUR EMBRYOS • G. Remuzzi LECT 21. VACCINE-PREVENTABLE DISEASES • A. Villani, E. Bozzola, A.C. Vittucci, A. Grandin, C. Di Camillo, L. Lancella LECT 22. WHAT IS NEW IN PATENT DUCTUS ARTERIOSUS TREATMENT? • F. Bardanzellu, P. Neroni, A. Dessì, M.A. Marcialis, V. Fanos LECT 23. NEW PROSPECTS FOR PEDIATRIC RESPIRATORY MEDICINE FROM METABOLOMICS • M. Stocchero, G. Giordano, P. Pirillo, E. Priante, S. Carraro, E. Baraldi LECT 24. NEW BIOMARKERS AND "OMICS" IN PREECLAMPSIA • M. Mussap, C. Ierace LECT 25. MATERNAL MILK: IMMUNOMICS AND MICROBIOMICS • D.G. Peroni LECT 26. NUTRIMETABOLOMICS OF MILK: COLOSTRUM AND MORE • A. Dessì, R. Pintus, F. Cesare Marincola, V. Fanos LECT 27. AUTISM FROM CONVENTIONAL DIAGNOSIS TO METABOLOMICS: URINARY METABOLOMICS PROFILE IN A POPULATION OF CHILDREN WITH AUTISM SPECTRUM DISORDERS • P. Curatolo, A. Noto, M. Siracusano, A. Riccioni, L. Mazzone, L. Barberini, V. Fanos, C. Fattuoni LECT 28. PLACENTAL BIOMARKERS • A.M. Paoletti, B. Piras, P. Abis, V. Corda, M. Neri, M.F. Marotto, M. Angiolucci, G.B. Melis, F. Coghe, V. Mais LECT 29. BIOMARKERS IN NEONATAL SEPSIS • R. Örs LECT 30. ACUTE KIDNEY INJURY IN NEWBORNS • C. Aygun LECT 31. BIOMARKERS IN CARDIOLOGY • G. Mercuro, P.P. Bassareo LECT 32. QUANTIFICATION IN NEONATAL URINE AND PROFICIENCY TESTING COMPARED TO NON-NMR METHODS • M. Spraul, H. Schäfer, C. Cannet, F. Fang LECT 33. ENHANCING IMMUNE RESPONSES IN CHILDREN WITH RECURRENT RESPIRATORY INFECTIONS • G.V. Zuccotti, C. Mameli LECT 34. OBSTETRICAL MANAGEMENT IN TWIN PREGNANCIES • E. Cosmi, L. Marin, S. Visentin LECT 35. THE PATHOLOGIST AND TWINS • D. Fanni, C. Gerosa, G. Faa LECT 36. TWINS: THE POWER OF EPIGENETICS • G. Corsello, A. Corsello LECT 37. MANAGEMENT OF PERINATAL LOSS OF TWINS • M. Puddu, E. Melis, V. Fanos LECT 38. NEUROPSYCHIATRIC PROBLEMS IN TWINS • M. Guarnieri, C. Ciampi LECT 39. SELF-REPORTED AGGRESSIVE BEHAVIOR IN HUMANS AND BIOMARKERS: A FOCUS ON LIPIDS AND METHYLATION • F.A. Hagenbeek, J. van Dongen, C.K. Kluft, L. Ligthart, G. Willemsen, E.J.C. de Geus, M. Bartels, D.I. Boomsma LECT 40. SOFT TISSUE TUMORS IN THE NEONATAL AND PEDIATRIC SETTING • R. Sciot LECT 41. PLACENTAL SOFT TISSUE TUMORS • G. Faa, C. Rossi, D. Fanni, E. Di Felice, V. Fanos, C. Gerosa LECT 42. DO OBSTETRICIANS REALLY KNOW PLACENTA? • S. Angioni LECT 43. ULTRASOUND AND PLACENTA • G. Monni, A. Iuculano LECT 44. MALE AND FEMALE PLACENTA: A REVOLUTION? • G. Faa, E. De Felice, C. Rossi, D. Fanni, V. Marinelli, V. Fanos, C. Gerosa LECT 45. DO NEONATOLOGISTS REALLY KNOW PLACENTA? • S. Perrone, M.G. Alagna, G. Buonocore LECT 46. S100B EXPRESSION IN PLACENTA • A. Faa, D. Fanni, C. Gerosa, G. Faa LECT 47. ACUTE CHORIOAMNIONITIS AND NEONATAL OUTCOME • C. Gerosa, C. Rossi, E. Di Felice, M. Angiolucci, V. Fanos, G. Faa LECT 48. METABOLOMICS AND PLACENTA • C. Fattuoni, L. Barberini LECT 49. ARTIFICIAL PLACENTA • S. Dessole, G. Capobianco, M. Dessole, C. Pini, A. Gulotta LECT 50. LOW DOSE MEDICINE: A NEW PHARMACOLOGICAL PARADIGM. FROM PRINCIPLES TO RESEARCH • S. Bernasconi, G. Bona LECT 51. REASONABLE USE OF ANTIBIOTICS IN PEDIATRIC AGE: ALTERNATIVE THERAPIES OR CONCURRENT THERAPIES? • G. Trapani LECT 52. NEONATAL SEIZURES: AN ITALIAN SURVEY ON CURRENT TREATMENT AND MONITORING PRACTICES • D. Pruna, R. Dilena, P. De Liso, M. Di Capua LECT 53. A TAILORED CLINICAL APPROACH TO THE TREATMENT OF MONOSYMPTOMATIC NOCTURNAL ENURESIS • G. Masnata, V. Manca, C. Guzzetti, F. Esu LECT 54. UNFORGETTABLE CASE REPORTS • F. Bardanzellu, M.E. Trudu, A. Atzei, G. Ottonello LECT 55. HIPS SONOGRAPHY IN THE THIRD MILLENIUM • M. Crisafulli, F. Piu, P. Balloi, R. Pintus, A. Dessì LECT 56. NEONATAL PHARMACOLOGY: WHAT'S THE NEWS? • L. Cuzzolin LECT 57. AIR NEONATAL TRANSPORTS IN SARDINIA: FROM STORK WINGS TO AIRPLAIN'S • A. Atzei, M. Puddu, G. Ottonello, V. Fanos LECT 58. MORE THAN 50 YEARS OF HOSPITAL FLIGHTS FOR THE ITALIAN AIR FORCE • Italian Air Force, 31st Wing, Captain D. Sgambati LECT 59. NEONATAL TRANSPORT IN ITALY AND BEYOND • S. Rugolotto LECT 60. A HEART OF... JERSEY • A. Brandi LECT 61. THE ITALIAN REFORM CONCERNING CIVIL AND CRIMINAL LIABILITIES IN THE HEALTH FIELD • F. Tregnaghi LECT 62. A MEDICO-LEGAL VIEW AT THE MEDICAL LIABILITY CONTEXT : LIGHTS AND SHADOWS OF THE ITALIAN "NEW LAW NUMBER 24/2017 GELLI-BIANCO" • F. Paribello, E. d'Aloja LECT 63. WHAT LEGAL MEDICAL RESPONSIBILITY FOR THE NEONATOLOGIST? • C. Romagnoli LECT 64. A NEW LAW ON PROFESSIONAL LIABILITY: BETWEEN UNSOLVED TANGLES AND ONGOING COMPLIANCE TO NEW RULES. THE ROLE OF SCIENTIFIC SOCIETIES • R. Agostiniani LECT 65. THE ROLE OF SCIENTIFIC SOCIETIES WITHIN THE FRAMEWORK OF THE NEW ITALIAN LEGISLATION ON PROFESSIONAL LIABILITY • G. Di Mauro LECT 66. THE NEW REALITY OF MEDICAL PROFESSIONAL RESPONSIBILITY IN ITALY • A. Canetto LECT 67. MEDICAL PROFESSIONAL ACCOUNTABILITY: THE NEW REALITY IN ITALY. THE OPINION OF THE PEDIATRIC SURGEON • L. Mascia LECT 68. A NEW APPROACH IS NEEDED FOR EFFECTIVE PREVENTION AND MANAGEMENT OF NEONATAL SKIN INJURIES • S. Tuccio, L. Guarinoni, L. Cirillo, L. Bruno, E. Duca, S. Zucchini, R. Memoli, D. Gerardini LECT 69. NURSING PRIORITIES TO NEWBORNS WITH DIGESTIVE OSTOMIES • M. Zicchi, S. Porcu, M.G. Pizzarri, A.R. Tanca, M. Ubertazzi, M.G. Olzai, M.G. Clemente LECT 70. INTEGRATING MICROBIOMICS AND METABOLOMICS DATA IN BEHAVIORAL COMPLEX TRAITS: A ROLE IN AGGRESSION? • M. Manchia, V. Fanos LECT 71. AGGRESSIVENESS FROM FETUS TO ADULT: THE TWINS CASE • R. Pintus, A. Dessì, A. Noto, V. Fanos LECT 72. DOHaD, NUTRITION AND BASIC RESEARCH • C. Mandò, I. Cetin LECT 73. ENVIRONMENTAL FACTORS AND EPIGENETIC MECHANISMS • L. Migliore LECT 74. PERINATAL PROGRAMMING AND BRAIN • V. Fanos, R. Pintus LECT 75. ANESTHESIA ON THE DEVELOPING BRAIN OF THE FETUS AND INFANT: THE DARK SIDE OF THE COIN • G. Finco, P. Mura LECT 76. EXPOSOMICS: ENVIRONMENT, EPIGENETIC FETAL PROGRAMMING AND PREVENTION OF CHRONIC PATHOLOGIES • E. Burgio, L. Migliore, I. Cetin, G. Faa, O. Forleo, F. Cesare Marincola, R. Pintus, A. Dessì, A. Noto, V. Fanos